Governance and Performance of Waste-to-Energy in Indonesia: A Comparative Review of Benowo and Putri Cempo - Syahrial Bairul Rochman; Achmad Husen; Ananto Kusuma Seta (Yayasan Ilomata, 2026)
Indonesia’s rapid growth in municipal solid waste generation has increased urgency for low-carbon waste management solutions. In response, the government has accelerated Waste-to-Energy development in 12 designated cities under Presidential Regulation No. 35/2018. This study applies a Systematic Literature Review following PRISMA 2020 guidelines to examine governance frameworks, environmental performance, and economic feasibility of Waste-to-Energy projects in Indonesia, with a comparative focus on the Benowo and Putri Cempo facilities. Literature was systematically retrieved from Scopus, ScienceDirect, SpringerLink, and Google Scholar using policy- and technology-related keywords. The search yielded 21 eligible publications between 2018–2025 that include empirical studies and policy-relevant documents. The results indicate that although both facilities operate under the same national regulatory framework, they differ in financing schemes, risk allocation, and operational efficiency. Benowo’s BOT model supported by tipping fees provides financial stability, whereas Putri Cempo’s DBFOT scheme requires higher operational efficiency due to the absence of municipal subsidies. Environmental assessments show that Benowo’s hybrid gasification and landfill gas system reduces greenhouse gas emissions by up to 57.1% from the pre-2015 level, while gasification at Putri Cempo achieves more than 85% waste reduction with lower emission intensity than conventional incineration. Economic feasibility is sensitive to waste quality, capacity utilization, and policy incentives. The novelty of this study lies in its integrated governance, environmental, and economic perspective linking national policy design with local implementation outcomes. The findings imply that stronger risk-sharing arrangements, improved waste segregation, and transparent environmental audits are essential to ensure sustainability of Waste-to-Energy development in Indonesia.